Design and experiment of the side insertion horizontal transplanting device for sweet potato (Ipomoea batatas Lam.) seedlings on mulch film - Zhang, Wanzhi; Zhu, Qian; Ge, Dameng; Zheng, Dehui; Zhang, Tingting (International Journal of Agricultural and Biological Engineering, 2024)
Side insertion horizontal transplanting sweet potato seedlings on mulch film is one kind of new planter pattern, which keeps the soil warm and moist restraining the infestation of pests and weeds, realizing dense transplanting and ensuring uniformity of sweet potato sizes. Therefore, a side insertion horizontal transplanting device for sweet potato seedlings on mulch film was designed, including the details and parameters of the reciprocating mechanism and the seedling clamping mechanism. Both the two mechanisms and the whole device were simulated and the test bench was built for field experiments to detect if this device can meet the agronomic requirements. The simulation results show that the designed device is in accordance with the agronomic requirements of horizontal transplanting, transplanting depth and transplanting length, and is potential for achieving rational close planting. The lateral length of the designed transplanting device is extended at about 90 mm compared with previous machine, which will promote the number of soil nodules of sweet potato seedlings and the growth of production enormously. The horizontal velocity of the transplanting claw is −17 mm/s when picking the seedling, the horizontal velocity of the transplanting claw 645 mm/s and the vertical velocity 83 mm/s when releasing the seedling. These data could ensure the accuracy requirements of horizontal transplanting trajectory. The field experiment results show the expulsion rate of sweet potato seedlings at 1.38%, the qualified rate of transplanting length and depth at 94.17% and 95.11% respectively, the average length and width of the mulch film breaking hole at 44.67 mm and 43.00 mm in several. The postures of the actual transplanted seedlings are consistent with the simulation results, meeting the requirements of horizontal transplanting with less damage to the mulch film. The designed transplanting device lays a foundation for the development of sweet potato seedlings side transplanting machine. Key words: sweet potato seedlings, Transplanting device, mechanism design, motion simulation, field experimentsDOI: 10.25165/j.ijabe.20231606.8360Citation: Zhang W Z, Zhu Q, Ge D M, Zheng D H, Zhang T T. Design and experiment of the side insertion horizontal transplanting device for sweet potato (Ipomoea batatas Lam.) seedlings on mulch film. Int J Agric & Biol Eng, 2023; 16(6):148–157.